Marketing Vis-a-Vis Revenue Generation in libraries and Information Centres: An Indian Experience - Shah, P.C. (DESIDOC Journal of Library & Information Technology, 2003)
The paper describes the importance of absorbing marketing principles and techniques in designing, generating and providing information products and services. An informative study of National lnformation Centre for Textile and Allied Subjects (NICTAS), describing its marketing and publicity activities as well as its future plans has been presented to illustrate the point that it is the adoption of marketing approach that will help Library and information Centres (LlCs), not only in their own self-sustenance but- also in the sustenance and self-sufficiency of their information products and services. http://dx.doi.org/10.14429/dbit.18.3.3396